A rational design strategy for an extremely deep-blue fluorescent emitter with a small CIE y value for solution processable, high efficiency, organic light-emitting diodes. (October 2017) - Reddy, Saripally Sudhaker; Sree, Vijaya Gopalan; Park, Ho-Yeol; Maheshwaran, Athithan; Song, Myungkwan; Jin, Sung-Ho
Abstract: A rational design strategy is proposed for synthesis of a new deep-blue emitter/dopant (denoted as TPA-3FA) based on triphenylamine (TPA) as the core with the addition of diethylfluorene/acridine analogues to frame a star-shaped material for solution processable high performance OLEDs. The photophysical, thermal, electrochemical, electronic, and hole transporting properties of TPA-3FA are examined. Most importantly, this rational design strategy of introducing diethylfluorene between TPA and acridine imparts high rigidity and non-planarity, which in turn completely suppress intermolecular interactions, and thus yields a strong narrow deep-blue fluorescence with a high quantum yield. Moreover, a solution processed non-doped device with TPA-3FA as an emitter exhibits excellent device performance with a maximum external quantum efficiency (EQE) of 4.43%, CIE ( x, y ) coordinates of (0.153, 0.045) and good device stability. The device performance was significantly improved with an EQE of 6.11% and CIE ( x, y ) coordinates of (0.156, 0.049) after doping into a host. The same device when processed in a halogen-free solvent exhibited an impressive EL performance (EQE: 5.72%; CIE (0.157, 0.046)). Graphical abstract: Highlights: Rationally designed and synthesized an efficient deep-blue fluorescent emitter for solution processed OLEDs. A nondoped device exhibits an excellent device performance with an EQE of 4.43% and CIE ( x, y ) value of (0.153, 0.045). Doped device performance is dramatically improved EQE of 6.11%; CIE ( x, y ):(0.156, 0.049). In a halogen-free solvent-processed device is also showed EQE of over 5.7% with a small CIE y value.